2004
DOI: 10.1212/01.wnl.0000132635.75819.e5
|View full text |Cite
|
Sign up to set email alerts
|

White matter lesion progression

Abstract: There is neuropathologic evidence that confluent MRI white matter lesions in the elderly reflect ischemic brain damage due to microangiopathy. The authors hypothesize that measuring changes in the progression of white matter lesions as shown by MRI may provide a surrogate marker in clinical trials on cerebral small-vessel disease in which the currently used primary outcomes are cognitive impairment and dementia. This hypothesis is based on evidence that confluent white matter lesions progress rapidly as shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 47 publications
3
112
0
Order By: Relevance
“…Other studies have demonstrated the roles of these changes in normal aging (Davatzikos and Resnick, 2002;Yamamoto et al, 2005), cognitive function (Gunning-Dixon and Raz, 2003;Ylikoski et al, 1993), depression (Salloway et al, 1996), and dementia (Varma et al, 2002). These pathological changes in white matter are accompanied by lesions in the small perforating cerebral arteries (Inzitari, 2003;Schmidt et al, 2002Schmidt et al, , 2004van Swieten et al, 1991) and are related to the prevalence of peripheral atherosclerosis Pico et al, 2002). Most of these studies were based on visually detectable changes in the white matter (e.g., DWMH), occurring at relatively late stages in the development of pathological changes.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have demonstrated the roles of these changes in normal aging (Davatzikos and Resnick, 2002;Yamamoto et al, 2005), cognitive function (Gunning-Dixon and Raz, 2003;Ylikoski et al, 1993), depression (Salloway et al, 1996), and dementia (Varma et al, 2002). These pathological changes in white matter are accompanied by lesions in the small perforating cerebral arteries (Inzitari, 2003;Schmidt et al, 2002Schmidt et al, , 2004van Swieten et al, 1991) and are related to the prevalence of peripheral atherosclerosis Pico et al, 2002). Most of these studies were based on visually detectable changes in the white matter (e.g., DWMH), occurring at relatively late stages in the development of pathological changes.…”
Section: Discussionmentioning
confidence: 97%
“…Although the pathophysiology of WMH is not completely understood, the presence of cerebrovascular risk factors has clearly been associated with increased WMH [7,22], suggesting that WMH are considered part of the spectrum of vascular-related injury, one of the markers for chronic end organ damage of the brain due to tissue ischemia [8,29,34]. As for the influence of autonomic failure on peripheral organs, especially cardiac function, recent studies [20,33] reported that the majority of patients with MSA had target-organ damage of hypertensive heart disease, similar to that observed in essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, confluent WMHs are the only MRI correlates of cerebral SVD for which the requirement of a surrogate marker is fulfilled; progression of confluent white-matter lesions correlates with cognitive decline. 13,147 Amyloid and tau imaging with positron emission tomography could also be helpful to diagnose comorbidity with AD in the patients with mixed disease, 145 with the caveat that amyloid deposits can also be present in cognitively normal individuals. 146 Biochemical CSF studies provide the third axis of diagnosis; elevated albumin ratio indicates that the BBB is compromised, which is more likely to occur in SVD than in AD.…”
Section: An Approach To Targeted Treatment Trialsmentioning
confidence: 99%